Radiolabeling approaches of nanoparticles with 99mTc. (24th April 2013) - Psimadas, Dimitrios; Bouziotis, Penelope; Georgoulias, Panagiotis; Valotassiou, Varvara; Tsotakos, Theodoros; Loudos, George
Abstract : Nanomedicine applications have recently gathered great attention in terms of their revolutionary properties and multivalency. Nanoparticles (NPs) have proven useful owing to their size, surface and kinetics advantages, as well as their ability to be functionalized with targeting, imaging and therapeutic moieties. Nuclear medicine is actively involved in nano‐research innovative breakthrough efforts in multiple applications, through the radiolabeling of NP structures. There are several ways that NP‐radiolabeling can be approached depending on the radionuclide that is used and the NP type. The radiolabeling of NPs with the most widely and easily available radiometal, which is 99m Tc, is the focus of this review. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Nanoparticles have advantageous properties for application in various fields of medicine, e.g. drug delivery, imaging and hyperthermia. Nuclear medicine is actively involved in innovative breakthrough efforts, through the radiolabeling of nanoparticle moieties with 99m Tc, which can be performed via a variety of pathways.